2000
DOI: 10.1053/jhep.2000.18712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Leptin Exposure on Triglyceride Deposition in Rat Liver

Abstract: Leptin has recently been suggested to play a role in the pathogenesis of hepatic steatosis. Consequently, this study was designed to examine the direct effects of portal leptin on the intrahepatic lipid contents in the postabsorptive state. Rat livers (n ‫؍‬ 6 per group) were perfused in a recirculating system and portally infused with leptin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
4
18
1
Order By: Relevance
“…The current study demonstrates that leptin effects on liver lipid metabolism can be mediated by hepatic leptin receptors at physiological leptin concentrations, confirming observations from previous studies (14,15,51). Because we were unable to detect ObRb protein or mRNA (data not shown), similar to previous studies (26,52), it is most likely the predominant ObRa that mediates the lipid-lowering effects of leptin.…”
Section: Figsupporting
confidence: 91%
“…The current study demonstrates that leptin effects on liver lipid metabolism can be mediated by hepatic leptin receptors at physiological leptin concentrations, confirming observations from previous studies (14,15,51). Because we were unable to detect ObRb protein or mRNA (data not shown), similar to previous studies (26,52), it is most likely the predominant ObRa that mediates the lipid-lowering effects of leptin.…”
Section: Figsupporting
confidence: 91%
“…The histological mechanism of non alcoholic fatty liver disease (NAFLD) is yet not understood (18). In many of obese people, increase of hepatic triglyceride levels, causes hepatic steatosis (24). The aim of this study was to investigate the effects of high fat diet (30%) on NAFLD histologically, in order to achieve this objective, obese rat model was constituted by means of fatty diet administration.…”
Section: Discussionmentioning
confidence: 99%
“…A portal perfusion of leptin in rats induced hypertriglyceridemia and contributed to hepatic steatosis by increasing the levels of free fatty acids accumulation in the liver [31]. Lines of evidence indicated that leptin modulated proinflammatory responses induced by endotoxin (lipopolysaccharide; LPS) [32] or tumor necrosis factor-α (TNF-α) [33].…”
Section: Animal Modelsmentioning
confidence: 99%